The role of background music in the visitors’ experience of art exhibition: music, memory, and art appraisal - Loureiro, S. M. C.; Roschk, H.; Lima, F. (International Journal of Arts Management, 2019)
This study explores the effect of background music on the perception and memory of an art exhibition in two experiments involving art evaluation, memory and behavioural intentions. The first (N = 234), a laboratory experiment conducted in a virtual art gallery, shows that background music helps people remember artworks but negatively influences evaluation of them in terms of arousal, valence and liking. The second (N = 238), a field experiment conducted in seven art galleries, shows that the gallery experience facilitates behavioural intentions through the mediation of positive emotions and memory; background music again acts as an ambivalent stimulus, as it amplifies the link between memory and behavioural intentions while attenuating the link between pleasant arousal (i.e., the emotional evaluation component) and behavioural intentions. This study contributes to the literature by investigating an under-researched subject (experiencing art). It shows that, contrary to the results reported in the literature, music may have adverse effects. It also expands the stimulus-organism-response model by introducing memory into atmospheric research on music. Art galleries can benefit from the favourable effects of music, but the music needs to match the style of the artwork so that its stimulus does not overlap that of the art.